(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2023)
The palaeoclimatic and palaeoenvironmental data obtained by the study of the Buco del Frate cave small-mammals indicate that, around 40,000 years ago (MIS3), the eastern part of the province of Brescia, immediately to the west of Lake Garda, was characterised by the presence of open taiga environment and watercourses crossing the plain facing the cave. Specifically, the palaeoclimatic conditions of this part of north-western Italy around 40,000 years ago – compared to climate data for the years 1960-90 measured at Ghedi, 20 km southwest of the Buco del Frate cave – involved average temperatures some 4° C cooler and rainfall some 30% lower. Based on the collected data we show that the western part of the Po Valley, west of Lake Garda, was characterized by a steppe-like environment, not too different from the almost contemporaneous site of Settepolesini di Bondeno (Ferrara), defined as "mammoth steppe". We also note that the western Po Valley, if compared with deposits from high- and medium-mountain contexts in the same area, was characterized by a more steppe-like environment. Indeed, the mountain settings, in perhaps more sheltered areas, indicate the presence of environments with more trees (or, at least, bushes).